Gender Differences in Political Career Progression: Evidence from U.S. Elections - Ryan Brown; Hani Mansour; Stephen O'Connell; James Reeves (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper establishes the presence of a substantial gender gap in the relationship between state legislature service and the subsequent pursuit of a Congressional career. The empirical approach uses a sample of mixed-gender elections to compare the differential political career progression of women who closely win versus closely lose a state legislature election relative to an analogous impact for men who closely win or lose a state legislature election. We find that the effect of serving a state legislative term on the likelihood of running for a Congressional seat is twice as large for men as women, and its effect on winning a Congressional race is five times larger for men than women. These gaps emerge early in legislators' careers, widen over time, and are seen alongside a higher propensity for female state legislators to recontest state legislature seats. This gender gap in advancing to Congress among state legislators is not generated by gender differences in previously accumulated political experience, political party affiliation, or constituency characteristics. After investigating several explanations, we conclude that the gender gap in political career progression is consistent with the existence of a glass ceiling in politics.
Keywords: D72; J16; J24; J71; 330; gender gap; politicians; discrimination